Implikasi Penerbitan Sukuk Terhadap Kinerja Keuangan dan Kesejahteraan Karyawan (Studi Pada Bank Muamalat Indonesia) - Miftahul Hasanah (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2018)
Nowadays, Islamic financial concept has been comprehensively accepted in the world and become an alternative for market that want shariah compliance. One of shariah financial instrument issued by states and corporates is sukuk. Sukuk is an interfaith financial institution cross cultur, and state that now become part of world financial system. And in Indonesia, Muamalat Bank is a first Islamic Banking institution that issued sukuk with e mission Rp 200 bilion on 2003. Furthermore, on 2008 with emission in the amount Rp 314 bilion, on 2012 with emission Rp 700 bilion.The study aims to empirically test the variables of the research, which has been formulated in the formulation problems. Wether there are implication between issuance of sukuk (X) toward the financial performance (Y1) and employee’s well-being (Y2) at the Bank Muamalat Indonesia. This research, use secondary data with the time series data based on financial statement of BMI 2000-2014. The analyzis performed by Structural Equation Model (SEM), reflective model. Furthermore, the testing of the hypotesis is done with the software of Smart Partial Least Square (PLS) in 3 version.